A Just and Green Recovery: Reflections on Catholic Social Teaching in Light of the Pandemic - Rowe, Gareth (Liberatio, 2024)
The paper poses the question: What would lead to a better and greener post-Covid world in terms of livelihoods and economics? Is this consistent with Catholic social teaching (CST) or a challenge to CST? The paper provides the first external report on a project currently being undertaken by CAFOD (part of Caritas Internationalis) with Durham University. The project undertakes an exploration of one of CAFOD’s priority themes: “a just, green global recovery.” It aims to reflect theologically on the pandemic and how it disrupted economic enabling environments and exacerbated structural inequalities and to suggest some ways forward as and when we begin to emerge from the pandemic. The overall aim of the project is to contribute towards advancing the vision of progress and agenda for change in CAFOD’s strategic framework: Our Common Home (OCH), which was itself inspired by Laudato Si’ and Pope Francis’s insight that “We are faced not with two separate crises, one environmental and the other social, but rather with one complex crisis which is both social and environmental.” Methodologically, the project aims at a multi-layered approach. A grassroots approach is central, building theology up from the voices of CAFOD’s partners. Discussions are being held with partners in Africa, Asia and Latin America to find out what kind of economic enabling environment would improve their lives. This approach is being supplemented by discussions with supporter groups in the UK. The insights from partners will be reflected upon in the light of CST in its widest sense. This includes the papal magisterium, regional episcopal conferences and the insights of liberation theologians.